Large variations in atrial fibrillation screening practice after ischemic stroke and transient ischemic attack in Sweden: a survey study - Kajsa Strååt; Eva Isaksson; Ann Charlotte Laska; Elisabeth Rooth; Emma Svennberg; Signild Åsberg; Per Wester; Johan Engdahl; on behalf of AF SPICE steering committee (BMC Neurology, 2024)
Abstract Background Atrial fibrillation (AF) screening after ischemic stroke or transient ischemic attack (TIA) is given high priority in clinical guidelines. However, patient selection, electrocardiogram (ECG) modality and screening duration remains undecided and current recommendations vary. Methods The aim of this study was to investigate the clinical practice of AF screening after ischemic stroke or TIA at Swedish stroke units. In collaboration with the stakeholders of the Swedish Stroke Register (Riksstroke) a digital survey was drafted, then tested and revised by three stroke consultants. The survey consisted of 17 multiple choice/ free text questions and was sent by e-mail to the medical directors at all stroke units in Sweden. Results All 72 stroke units in Sweden responded to the survey. Most stroke units reported that ≥ 75% of ischemic stroke (69/72 stroke units) or TIA patients (67/72 stroke units), without previously known AF, were screened for AF. Inpatient telemetry ECG was the method of first-choice in 81% of the units, but 7% reported lack of access. A variety of standard monitoring durations were used for inpatient telemetry ECG. The second most common choice was Holter ECG (17%), also with considerable variations in monitoring duration. Other AF screening modalities were used as a first-choice method (handheld and patch ECG) but less frequently. Conclusions Clinical practice for AF screening after ischemic stroke or TIA differed between Swedish stroke units, both in choice of AF screening methods as well as in monitoring durations. There is an urgent need for evidence and evidence-based recommendations in this field. Trial registration Not applicable.